Lonely Individuals Do Not Show Interpersonal Self-Positivity Bias: Evidence From N400 - Zhu, Min; Zhu, Changzheng; Gao, Xiangping; Luo, Junlong (Frontiers in Psychology, 2018)
Self-positivity bias is one of the well-studied psychological phenomena, however, little is known about the bias in the specific dimension on social interaction, which we called herein interpersonal self-positivity bias—people tend to evaluate themselves more positively on social interactions, prefer to be included rather than to be excluded by others. In the present study, we used a modified self-reference task associated with N400 to verify such bias and explore whether impoverished social interaction (loneliness) could modulate it. Findings showed that exclusion verbs elicited larger N400 amplitudes than inclusion verbs, suggesting that most people have interpersonal self-positivity bias. However, loneliness was significantly correlated with N400 effect, showing those with high scores of loneliness had smaller differences in the N400 than those with lower scores. These findings indicated impoverished social interaction weakens interpersonal self-positivity bias; however, the underlying mechanisms need to be explored in future research.